2013
DOI: 10.1371/journal.pone.0083544
|View full text |Cite|
|
Sign up to set email alerts
|

Stimulus Phase Locking of Cortical Oscillation for Auditory Stream Segregation in Rats

Abstract: The phase of cortical oscillations contains rich information and is valuable for encoding sound stimuli. Here we hypothesized that oscillatory phase modulation, instead of amplitude modulation, is a neural correlate of auditory streaming. Our behavioral evaluation provided compelling evidences for the first time that rats are able to organize auditory stream. Local field potentials (LFPs) were investigated in the cortical layer IV or deeper in the primary auditory cortex of anesthetized rats. In response to AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 81 publications
1
26
0
Order By: Relevance
“…Our phase analysis indicates that phase-shifts are random between both frontal and temporal areas. Phase-alignment can promote communication between brain regions or facilitate stimulus-related events (Noda et al 2013; Mercier et al 2015). In the present study, we do not observe consistent, significant phase relationships between areas.…”
Section: Discussionmentioning
confidence: 99%
“…Our phase analysis indicates that phase-shifts are random between both frontal and temporal areas. Phase-alignment can promote communication between brain regions or facilitate stimulus-related events (Noda et al 2013; Mercier et al 2015). In the present study, we do not observe consistent, significant phase relationships between areas.…”
Section: Discussionmentioning
confidence: 99%
“…Strong adaptation that can provide the basis for build-up was also observed in the tonotopic pattern of membrane potentials recorded using voltage sensitive dye imaging in the primary auditory cortex of the anaesthetized guinea pig [57]. Noda et al [37,62] reported rstb.royalsocietypublishing.org Phil. Trans.…”
Section: (D) Neural Correlate Of Build-up Of Stream Segregationmentioning
confidence: 84%
“…These state differences between inattentive animal and attentive human subjects make comparisons difficult. Finally, human electrophysiological studies apply non-invasive techniques reflecting the response of large populations of neurons [3] whereas the animal studies rarely look at simultaneously recorded populations of neurons a time [37,57,62], nor have done so at the level of individual neurons. This so far precluded direct observation of anti-correlated neuronal response patterns as are predicted by the temporal coherence hypothesis for the formation of auditory streams [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of gamma oscillations for precise neural timing (Buzśaki & Wang, ; Cardin et al., ; Li, Morita, Robinson, & Small, ; Nikolić, Fries, & Singer, ) and perceptual binding (Engel & Singer, ; Ross & Fujioka, ) have been discussed in recent years. Beyond sensory encoding, the auditory evoked gamma response is involved central processes of extracting the meaning of sound, such as in perceptual organization of an auditory stream (Noda, Kanzaki, & Takahashi, ). The gamma response is generated in thalamocortical networks (Llinás, Leznik, & Urbano, ; Steriade, Contreras, Amzica, & Timofeev, ), and its amplitude depends on the balance between inhibition and excitation in cortical interneurons.…”
Section: Introductionmentioning
confidence: 99%